Björn Thorteinsson: Island. (1985). 312 s. Erik Helmer Pedersen: Pionererne. (1986). 338 s., 298,-kr. Sverre Bagge og Knut Mykland: Norge i dansketiden. (1987). 334 s., 298,kr. (Politikens Forlag). - Fode, Henrik (Historie/Jyske Samlinger, 1989)
-